HUBUNGAN AMAL WAJIB DENGAN SUNNAH - Siregar, Dame (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2018)
Charitable which is its law isobliged to sin leaving it and reward do/conduct him by up to standard and its foundation. Matter which issunnah may not the more percentage leave him, compared to conductingÂ  him . Law which is makruh because hateful makruh he/she said, ought to the more percentage leave it compared to conducting him. Charitable law which issunnah will complete lacking of religious service which isobliged to or which isfardu. Prayer sit amongÂ  two sujud ÙˆØ§Ø¬Ø¨Ø±Ù†ÙŠ ought to be practiced by which is sunnah, otherwise hence inappropriate among word with deed. Difference among word with deed of hateful by matter of Subhanahu ta'ala wa Allah.